Tracing the Epic Tradition in The Fantaserye: GMA 7’s “Encantadia” As an Epic - Sekito, Ralph Edward Paulo (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2020)
Popular culture is an emergent study compared to other disciplines. Studies on television as more than a means of entertainment are scarce. As such, this paper is an attempt to fill that dearth by looking into the fantaserye and its relationship with the traditional conventions of the epic. Through the theories on the conventions of the epic and the function of the epic hero propounded by Damiana Eugenio and Isagani Cruz respectively, the researcher looks into the possibility that the fantaserye is inspired from the traditional epic. John Fiske and John Hartley’s notion on television as today’s bard was also utilized in this study. The method used throughout the study is Content analysis. Results show that the fantaserye and the folk epics have similar attributes such as having the epic hero, their travails and adventures, and their physical and moral transformations that embody the group’s beliefs, ideals, and aspirations, although one difference is that the folk epics are either chanted orally and or performed, while the fantaserye “Encantadia” is aired through the aid of the television. And lastly, some characters were inspired from traditional Filipino folk epics and neighboring countries. To conclude, the fantaserye gets its materials and inspiration not only from mythological tales, but also from the folk epics, thus making oral literature survive in another form, but at the same time deviates from these inspirations which makes it a postmodern take of the traditional epic. This proves that the popular culture as a field of study that can be associated to other similar fields such as literary studies. Also, the folk epic did not die a natural death in the oral tradition; it adapted through a medium which is relevant and accessible to all: the television.